TRANSFORMATION OF JUVENILE DELINQUENCY AMONG GEN Z: BETWEEN PHYSICAL SPACE AND THE VIRTUAL WORLD - Nadya Grestyana; Melia Sintha; Vivi Friskila Angela; Gradila Apriani; Iin Aprillina (RADJA PUBLIKA, 2026)
This research discusses the transformation of juvenile delinquency among Generation Z from physical spaces to digital environments. Modernization and technological advancements have shifted delinquent behavior from traditional acts such as street brawls to virtual actions like cyberbullying, dissemination of harmful content, and identity manipulation. Data indicates a 65% increase in digital-based juvenile delinquency cases over the past five years, with 92% of teenagers accessing the internet for an average of 7 hours per day. Contributing factors include low digital literacy, lack of parental supervision, social media algorithm influence, and weak regulatory frameworks. This study analyzes the distinct characteristics of delinquency in both physical and digital domains and proposes comprehensive strategies for prevention, such as integrating character education, enhancing digital literacy, and fostering multi- stakeholder collaboration. The phenomenon calls for a redefinition of the roles of educational institutions and increased parental involvement in shaping resilient digital character. A cross-sectoral approach is essential to develop a generation that is both technologically adept and morally grounded.